SPIRITUALITAS DZIKIR AL-MA’TSURAT HASAN AL-BANNA (STUDI LIVING QUR’AN PADA UKMK LDK REFAH UIN RADEN FATAH) - Eko Pranata; Halimatussa'diyah; RA. Erika Septiana (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
This article aims to examine the spirituality of dhikr al-Ma'tsurat at UKMK LDK Refah UIN Raden Fatah. This is motivated by UIN Raden Fatah students who are active in UKMK LDK Refah, namely they do recitations of dhikr al-Ma'tsurat which are routinely read every morning and evening, even before carrying out the agenda in UKMK. By using qualitative methods and types of field research, as well as the Living Qur'an approach, this article concludes that dhikr al-ma'tsurat contains spiritual values, namely; presenting love to Allah, pleasure towards His qadha and qadar, and fostering humility. Dhikir al-Ma'tsurat can also provide various benefits for the UKMK LDK Refah Cadres who regularly read it, namely: first, Allah will protect against satanic interference, because in al-Ma'tsurat there are verses of the chair and letter of al-Baqarah. Second, you will get intercession from Rasulullah SAW, because in al-Ma'tsurat there is also a prayer chant. Third, it will be an expiation for sins, because in al-Ma'tsurat there are readings of istighfar, tahmid, tahlil, as well as prayers asking forgiveness from Allah. Fourth, it will make the heart always feel calm, because reading al-Ma'tsurat will lead to always remembering Allah in every condition.